All together now: Cellular and molecular aspects of leaf development in lycophytes, ferns, and seed plants - Romanova, Marina A.; Domashkina, Valentina V.; Maksimova, Anastasiia I.; Pawlowski, Katharina; Voitsekhovskaja, Olga V. (Frontiers in Ecology and Evolution, 2023)
Recent advances in developmental genetics together with accumulation of transcriptomic data of plants from divergent lineages provide an opportunity to unravel the evolution of plant morphology. To understand leaf origin in sporophytes of land plants we have combined the available molecular and structural data on development of leaves with different morphologies in different plant taxa: club mosses, spike mosses, leptosporangiate ferns, ophioglossioid ferns, marattioid ferns, whisk ferns, horsetails and conifers. Specifically, we address the peculiarities of proximo-distal, ad/abaxial and lateral development; presence/absence of mesophyll differentiation into palisade and spongy parenchyma; and type of leaf vascular bundles (collateral, bicollateral or amphicribral, respectively). Furthermore, taxon-specific and morphology-specific features of leaf development are considered in the context of the organization of shoot apical meristems (SAMs): monoplex, simplex or duplex. The data available imply that cellular pattern of leaf initiation correlates with the structure of the SAMs, but the later stages of leaf development are not. Occurrence and, if available, patterns of expression of homologues of the angiosperm genes responsible for the development of adaxial (ARP and C3HDZ) and abaxial (YABBY and KANADI) leaf domains, or establishment of the leaf marginal meristem (WOX) are discussed. We show that there is no correlation in the set of homologues of TFs that regulate abaxial and adaxial leaf domain development between leaves containing only spongy mesophyll (of spike mosses, club mosses, whisk ferns, horsetails and most conifers), and between leaves differentiated into palisade and spongy mesophyll (of leptosporangiate ferns, Ginkgo, Gnetum and angiosperms). Expression of three out of four regulators of leaf development in primordia of both leaves and sporangia – C3HDZ in spike mosses and whisk ferns, YABBY in club mosses and KANADI in spike mosses and horsetails – indicates that a sporangium developmental program could have been co-opted as a "pre-program" for the origination of microphylls and euphylls. Additionally, expression of regulators of leaf development regulators in SAMs of spike mosses (ARP, C3HDZ and KANADI), club mosses (YABBY), leptosporangiate ferns (C3HDZ) and horsetails (C3HDZ and KANADI) indicates that at least some mechanisms of SAM regulation were as well co-opted in the pre-program of leaf precursors.